Examining tourist satisfaction and dissatisfaction of the existing vegetarian and vegan restaurants in Romania - Elekes, Andra-Henrietta (2020)
With the growth of vegetarianism and veganism worldwide, the restaurant industry in Romania ought to adapt and react proactively to the needs of this evolving market segment. However, a gap has been identified in the literature regarding the understanding of their needs and wants. Academic research failed to inquire into the complex subject of what do vegetarians of vegans expect to find in a restaurant setting. Therefore, this dissertation examined the satisfaction and dissatisfaction motives of vegetarians and vegans regarding the quality of vegetarian and vegan restaurants in Romania. The aim and objectives of this research were met through a qualitative approach, using semi-structured interviews and thematic analysis of interview transcripts to determine the aspects driving tourists’ satisfaction and dissatisfaction of the current offerings. The research produced a number of key findings, showing that aspects driving dissatisfaction prevail, especially the lack of menu variety; the lack of diversity of the types of vegetarian or vegan restaurants; the inaccessible prices and opening hours, as well as the poor marketing strategies of these restaurants and the presence of non-vegan staff. The main conclusion drawn from the findings is that the restaurant industry in Romania is yet unprepared to cater for the needs of a growing vegetarian or vegan tourist mass, as it is still far from reaching the superior standards of vegetarian or vegan restaurants abroad. This research argues that restaurant managers should acknowledge that the needs of vegetarian or vegan customers may differ from those of meat-eaters, should enhance their offering in order to provide a total customer experience and stop assuming that these clients will be satisfied merely with plant-based food options in the menu.